Formulate and Evaluate an Osmotic Drug Delivery System of Propranolol Hydrochloride Drug by the Pores Formed in situ and by Avoiding Laser Drilling of Tablets and Risk of Orifice Blocking - Jaswitha, Tirumalasetti (International Journal of Pharmaceutical & Biological Archive, 2021)
The present investigation embodies the development of micro porous osmotic pump of B.C.S class-1 molecule mainly with an objective to deliver a prolong time or to maintain controlled release of drug for an extended duration. Core of osmotic tablet was prepared by direct compression using drug, osmogen, release retardant, and on rotary compression machine. Core tablets were coated using cellulose acetate as semi permeable membrane and PEG 400 as pore former dissolved in 9:1acetone: watermixture. Totally six formulations were prepared. All tablets were evaluated for physical parameters such as weight variation, hardness, friability, thickness, and in vitro drug release. Trails F1, F2 were formulated by using sodium acetate as osmogen with 80 mg, 120 mg, and these are coated as for procedure and the study the effect of osmogen concentration on drug release was studied and osmogen concentration was optimized. 120 mg sodium acetate, that is, 80 mg per tablet showed controlled release for 10 h and hence taken as optimized but it does not attains flow properties and assay valve. Trails F3, F4 were formulated using potassium chloride as osmogen with 80 mg, 120 mg and these are coated as for procedure and the study the effect of osmogen concentration on drug release was studied and osmogen concentration was optimized. 120 mg potassium chloride, that is, 80 mg per tablet showed controlled release for 8 h and hence taken as optimized but it does not attain longer time. Trails F5, F6 were formulated by using mannitol as osmogen with 80 mg, 120 mg and these are coated as for procedure and the study the effect of osmogen concentration on drug release was studied and osmogen concentration was optimized. 120 mg mannitol, that is, 80 mg per tablet showed controlled release for 12 h and hence taken as optimized.